1997
DOI: 10.5636/jgg.49.supplement_s187
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Spectra of Wind Velocity Fluctuations between 1 hour and 1 month in the Atmospheric Boundary Layer over Equatorial Indonesia

Abstract: Frequency power spectra are analyzed from zonal and meridional wind velocities observed continuously in a height range below 2.5 km with the Kyoto University Boundary Layer Radar (BLR) in Serpong, Indonesia (6.4°S, 106.7°E). We find that (i) the spectral slope in a period range from a few hours to a few days is approximately -1; (ii) the power spectral densities in the rainy season are at least about two times larger than those in the dry season; (iii) the diurnal component is dominant both in dry and rainy se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Since November 1992, the RASC (Radio Atmospheric Science Center) of Kyoto University, Japan in collaboration with BPPT (Agency for Assessment and Application of Technology), and LAPAN (National Institute of Aeronautics and Space), Indonesia, has been continuously carrying out three-dimensional wind observations of high-resolution, in altitude and in time (100m and 1min) in the lower troposphere (0.3-3.2km altitude), at Serpong near Jakarta, Indonesia (6.4oS, 106.7oE), using a 1357.5MHz Boundary Layer Radar (BLR) (Hashiguchi et al, 1995a). Hashiguchi et al (1995b) have shown wind and rainfall disturbances with periods of a few days or longer, and Hashiguchi et al (1997) have done frequency spectral analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since November 1992, the RASC (Radio Atmospheric Science Center) of Kyoto University, Japan in collaboration with BPPT (Agency for Assessment and Application of Technology), and LAPAN (National Institute of Aeronautics and Space), Indonesia, has been continuously carrying out three-dimensional wind observations of high-resolution, in altitude and in time (100m and 1min) in the lower troposphere (0.3-3.2km altitude), at Serpong near Jakarta, Indonesia (6.4oS, 106.7oE), using a 1357.5MHz Boundary Layer Radar (BLR) (Hashiguchi et al, 1995a). Hashiguchi et al (1995b) have shown wind and rainfall disturbances with periods of a few days or longer, and Hashiguchi et al (1997) have done frequency spectral analysis.…”
Section: Introductionmentioning
confidence: 99%